EFISIENSI PEMBERIAN ONGGOK TERFERMENTASI Trichoderma viride PADA AYAM KAMPUNG SUPER (Gallus domesticus sp)TERHADAP EFISIENSI PAKAN & IOFC - Fani Kurniawan; Alfan Setya Winurdana; Eddy Trijana Sudani (Universitas Islam Balitar, 2020)
ABSTRACT This study was purposed to determine the influence of the addition of feremented cassava waste by Trichoderma viride fungus towards feed efficiency and IOFC of kampong chicken production. The material used in this research was 120 unit of kampong chicken at the age of 28 days. The given treatments were: 1 feed treatment was 100%. 2 feed treatment was 75% and fermented cassava waste was 25%. 3 feed treatment was 50% and fermented cassava waste was 50%. 4 feed treatment was 25% and fermented cassava waste was 75%. The observed variables were feed efficiency and IOFC. The data were processed using complete random design analysis. If there was a significant difference, Least Significant Different follow-up test will be conducted. The research result showed feed efficiency (P<0.05) and IOFC (P<0.05). The addition of fermented cassava waste in the feed of kampong chicken is no affects the feed efficiency and IOFC.